Effectiveness of monovalent rotavirus vaccine against hospitalizations due to all rotavirus and equine-like G3P[8] genotypes in Haiti 2014–2019. Issue 32 (22nd July 2021) - Burnett, Eleanor; Juin, Stanley; Esona, Mathew D.; Desormeaux, Anne Marie; Aliabadi, Negar; Pierre, Manise; Andre-Alboth, Jocelyn; Leshem, Eyal; Etheart, Melissa D.; Patel, Roopal; Dely, Patrick; Fitter, David; et al.
Abstract: Background: Rotavirus vaccines are effective in preventing severe rotavirus. Haiti introduced 2-dose monovalent (G1P[8]) rotavirus vaccine recommended for infants at 6 and 10 weeks of age in 2014. We calculated the effectiveness of rotavirus vaccine against hospitalization for acute gastroenteritis in Haiti. Methods: We enrolled children 6–59 months old admitted May 2014-September 2019 for acute watery diarrhea at any sentinel surveillance hospital. Stool was tested for rotavirus using enzyme immunoassay (EIA) and genotyped with multiplex one-step RT-PCR assay and Sanger sequencing for stratification by genotype. We used a case-negative design where cases were children positive for rotavirus and controls were negative for rotavirus. Only children eligible for vaccination were included and a child was considered vaccinated if vaccine was given ≥ 14 days before enrollment. We used unconditional logistic regression to calculate odds ratios and calculated 2-dose and 1-dose vaccine effectiveness (VE) as (1 - odds ratio) * 100. Results: We included 129 (19%) positive cases and 543 (81%) negative controls. Among cases, 77 (60%) were positive for equine-like G3P[8]. Two doses of rotavirus vaccine were 66% (95% CI: 44, 80) effective against hospitalizations due to any strain of rotavirus and 64% (95% CI: 33, 81) effective against hospitalizations due to the equine-like G3P[8] genotype. Conclusions: These findings are comparable to other countries in the Americas region. To the best of our knowledge, this is the first VE estimate both against the equine-like G3P[8] genotype and from a Caribbean country. Overall, these results support rotavirus vaccine use and demonstrate the importance of complete vaccination.